Colorimetric Sensors: Temperature‐Activated Reverse Sensing Behavior of Pd Nanowire Hydrogen Sensors (Small 2/2013). Issue 2 (21st January 2013) - Yang, Dachi; Valentín, Luis; Carpena, Jennifer; Otaño, Wilfredo; Resto, Oscar; Fonseca, Luis F.
<x xml:space="preserve">Abstract</x> The image shows an artistic version of a Pd nanowire surrounded by hydrogen molecules. The nanowire is electrically connected to the Pt electrodes of a sensor device by L. F. Fonseca and co‐workers to study the effects of reduced temperature on its electrical response during hydrogen gas exposure. The TEM image shows the ordered crystal structure of the material. As described on page 188, when temperature is reduced, a crossover from a bulk‐ to a percolationcontrolled response is observed. This effect was confirmed in nanowires arrays on interdigitated electrodes and single nanowires integrated to MEMS devices. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>